2006
DOI: 10.1080/01612840600842642
|View full text |Cite
|
Sign up to set email alerts
|

Health Responses of New York City Firefighter Spouses and Their Families Post-September 11, 2001 Terrorist Attacks

Abstract: Much attention has been focused on New York City firefighters and their responses to the traumatic events of the September 11, 2001, terrorist attacks on the World Trade Center, given their extensive involvement in rescue efforts, and the overwhelming loss of life among the fire department employees. It quickly became evident that the impact of this horrendous event had resonated deeply not only on the families and children of the firefighters who gave their lives, but also on those who had survived. The goal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 13 publications
1
45
0
Order By: Relevance
“…A few interviewees mentioned that they would prefer not to talk to their family because of the distressing nature of incidents they work with and to avoid their families worrying about them at work. Similar findings were reported by Menendez et al (2006) and Yoo and Matsui (2012).…”
Section: Theme 4: Moderatorssupporting
confidence: 81%
“…A few interviewees mentioned that they would prefer not to talk to their family because of the distressing nature of incidents they work with and to avoid their families worrying about them at work. Similar findings were reported by Menendez et al (2006) and Yoo and Matsui (2012).…”
Section: Theme 4: Moderatorssupporting
confidence: 81%
“…Menendez et al [32] conducted semi-structured focus groups of women whose firefighter husbands were directly involved in rescue efforts at Ground Zero. An analysis of transcripts from interviews reveals the nature and extent of the impact of the trauma on these women, their husbands, and their children.…”
Section: Impact On Familiesmentioning
confidence: 99%
“…Prior studies have documented psychological sequelae in the spouses of military veterans [2], rescuers and responders [35], and peace makers [6], but only one of these studies examined biological stress measures [5]. Pfefferbaum et al [5] found autonomic reactivity in a small nonrepresentative sample of spouses of firefighters who responded to the Oklahoma City bombing; their study did not use a comparison sample and did not examine HPA axis functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Research has examined the spouses of military veterans [2], rescuers, and responders [35] and peace makers [6]. The experiences and consequences of trauma in terrorism victims and their spouses may differ from those of military veterans, rescuers and responders, and peace makers in several ways: (1) responders and service personnel have been selected, or have self selected, for involvement in the activities that resulted in their trauma exposure presumably with selection based on certain strengths; (2) these individuals typically undergo training which may enhance their coping and resilience; (3) they are able to anticipate their involvement in such events; and (4) they are likely to see themselves in a helping role rather than as primary victims of an event.…”
Section: Introductionmentioning
confidence: 99%